Improvements in Photocatalytic Activity in Visible Light Destruction of Chlorpyrifos in a Batch Reactor Applying the Z-Scheme g-C3N4/Fe3O4/CuWO4/CuO Heterojunction, Including Fabrication, Characterization, and Recycling - Shno M. Ali; Abeer I. Alwared (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
The most widely used pesticide in agricultural regions across the entire globe is chlorpyrifos (CPF).In the present research, g-C3N4/Fe3O4/CuWO4/CuO heterojunction has been created through a series of straightforward technologies and used for photocatalytic degradation of chlorpyrifos .The produced g-C3N4/Fe3O4/CuWO4/CuO nanocomposites' optical and magnetic features, structure, and morphologies have been investigated using XRD, FTIR, elemental mapping, EDS, SEM, TEM, VSM, DRS, PL, and BET methodologies. With rate constants of 0.00507 and 0.00696 min-1, correspondingly, the photocatalyst enabled the photocatalytic degradation of chlorpyrifos, g-C3N4, and CuWO4, which achieved maximal efficiencies of 50% and 69% in visible light. However, under visible light, g-C3N4/Fe3O4/CuWO4/CuO exhibited a maximum performance of 93% with rate constants of 0.0159 min-1. In order to remove chlorpyrifos from aqueous solution, this work created a unique type of g-C3N4/Fe3O4/CuWO4/CuO nanocomposite utilizing a multistage procedure using a photocatalytic technique employing novel catalysts. Being exposed to visible light, the as-fabricated g-C3N4/Fe3O4/CuWO4/CuO substantially enhanced the photocatalytic activity for the successful elimination of pesticide, boosting its potential for use in ecologically friendly water purification systems. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).